Cryoprotectant role of exopolysaccharide ID1 in the vitrification/in‐straw warming of in vitro‐produced bovine embryos. (12th July 2022) - Martínez‐Rodero, Iris; Salas‐Huetos, Albert; Ordóñez‐León, Alina; Hidalgo, Carlos Olegario; Yeste, Marc; Mercadé, Elena; Mogas, Teresa
Abstract: The cold‐adapted bacterium Pseudomonas sp . ID1 produces the extracellular exopolysaccharide ID1 (EPS ID1) with cryoprotective activity. This study was designed to optimize the vitrification/in‐straw warming protocol of in vitro ‐produced (IVP) blastocysts by adding EPS ID1 to the vitrification media. Day 7‐expanded blastocysts were vitrified/warmed using the VitTrans device after the addition of 0 or 100 μg/mL EPS ID1 to the vitrification media. Blastocysts vitrified by the Cryotop method and fresh non‐vitrified blastocysts served as controls. Outcomes were assessed in the warmed embryos in terms of survival rates and mRNA relative abundances of BAX, BCL2, GPX1, and CDX2 genes . No differences in survival rates were observed at 3 h post‐warming between vitrification treatments. At 24 h post‐warming, the addition of EPS prior to vitrification with the VitTrans device produced similar survival rates to Cryotop‐vitrified embryos and similar hatching rates to fresh non‐vitrified or Cryotop‐vitrified embryos. No differences emerged in BCL2 gene expression. Lower BAX ( p < .05) and higher GPX1 ( p < .05) and CDX2 ( p < .1) gene expression were observed in expanded and/or hatched blastocysts derived from VitTrans‐EPS‐vitrified embryos when compared to those from the non‐supplemented group. In conclusion, addition of EPS not only promoted blastocyst survival and hatching after VitTrans vitrification/warming but also modified the expression of genes associated with better embryo quality.